Islam in China history, spread and culture : a pictorial book - Koya, P.K (Islamic Book Trust, 2019)
This book, through its rich and abundant collection of fourteen centuries of pictorial illustrations, takes us on a journey of discovery through history, culture, architecture and an overall look at the historical ancestry of Muslims in China. It also draws attention to the spread of Muslim settlements across the landscape of China. The themes also bring us nearer home to Malaysia and an overall look at Islam's historical contact with the Malay archipelago where a variety of religious faiths have harboured in our midst for centuries, interacting and assimilating each other's socio-cultural practices and heritage. The spread and adaptation of Islamic cultural civilisation across China through fourteen centuries of peaceful co-existence we can in many ways find affinity with China's historical experience. It is our hope that this book will open the readers' eyes and minds yet a little more on people and land beyond our borders, especially of Islam In China.